ROEMOLEX - A ROMANIAN EMOTION LEXICON - BRICIU, Anamaria; LUPEA, Mihaiela (Studia Universitatis Babeș-Bolyai Informatica, 2017)
In Natural Language Processing tasks, semantical and lexical resources are of paramount importance for efficient implementations of solutions. However, availability of tools for any other language than English is fairly limited, therefore leaving the field open to improvements and new developments. This paper presents the second version of RoEmoLex, a lexicon containing approximately eleven thousand Romanian words tagged with a series of emotions and two valences. We describe the steps followed in the improvement process of the first version of the resource: the addition of new terms, and the extension of emotional concepts to finer-grained tags.